2007
DOI: 10.1007/s10899-007-9086-0
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Problem Gambling Among U.S. Adolescents and Young Adults: Results from a National Survey

Abstract: A random telephone survey was conducted with a representative sample of 2,274 U.S. residents aged 14-21. The prevalence of problem gambling, as measured by the SOGS-RA, was 2.1%. Sixty-eight percent (68%) of the respondents had gambled in the past year, and 11% had gambled more often than twice per week. Males had much higher gambling involvement than females, and gambling involvement increased among older respondents. Blacks were less likely than average to have gambled in the past year, but if they gambled, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
139
2
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(162 citation statements)
references
References 20 publications
17
139
2
4
Order By: Relevance
“…3 Further, prevalence research reveals approximately 9% to 19% of adolescents gamble for money on a frequent basis. [4][5][6] While for many adolescents, participation in risk or addictive behaviours does not result in serious negative consequences, those who are initiated into these behaviours at young ages are at elevated risk for alcohol-related problems in adolescence, [7][8][9][10] as well as nicotine dependence, 11 problematic alcohol consumption, 12 and at-risk gambling status 13 in young adulthood. The fact that early onset of risk and addictive behaviours is related to various problematic outcomes draws attention to the importance of identifying the precursors to the acquisition and development of these behaviours among children and pre-adolescents.…”
Section: Abré Gémentioning
confidence: 99%
“…3 Further, prevalence research reveals approximately 9% to 19% of adolescents gamble for money on a frequent basis. [4][5][6] While for many adolescents, participation in risk or addictive behaviours does not result in serious negative consequences, those who are initiated into these behaviours at young ages are at elevated risk for alcohol-related problems in adolescence, [7][8][9][10] as well as nicotine dependence, 11 problematic alcohol consumption, 12 and at-risk gambling status 13 in young adulthood. The fact that early onset of risk and addictive behaviours is related to various problematic outcomes draws attention to the importance of identifying the precursors to the acquisition and development of these behaviours among children and pre-adolescents.…”
Section: Abré Gémentioning
confidence: 99%
“…Research also has shown that individuals who are widowed, separated or divorced (Petry et al 2005), and individuals who begin gambling at a young age (Kessler et al 2008) are more susceptible to gambling problems than others. Further, there are correlations between gambling behavior and socio-economic status (SES): studies have found that individuals with a lower SES are at increased risk for gambling problems (Welte et al 2008).…”
Section: Sociological Factorsmentioning
confidence: 99%
“…Problem gambling is typically assessed using standardized scales that ask questions, for example, about gambling causing problems with family, with friends, or at work or school, or borrowing or stealing money to cover gambling debts and going back to recover losses ("chasing"). Problem gambling is often defi ned as endorsement of three or more problem items, and pathological gambling is classifi ed when fi ve or more problems or diagnostic criteria are endorsed (Welte et al, 2001(Welte et al, , 2008. From regional studies, there is evidence that gambling is prevalent among youth.…”
mentioning
confidence: 99%